Purification of and factors affecting 5'-phosphodiesterase from germinating adzuki (Vigna angularis L.) bean - Pui, Liew Phing (2012)
5’-Phosphodiesterase (5’-PDE) is an enzyme that hydrolyses RNA to form 5’-inosine monophosphate (5’-IMP) and 5’-guanosine monophosphate (5’-GMP) which function as flavour enhancers. The best producer of 5’-PDE was selected from germinated seeds, namely mung bean (Vigna radiate), soybean (Glycine max), adzuki bean (Vigna angularis L.), chick pea (Cicer arietinum), black eye pea (Vigna unguiculata) and petai (Parkia speciosa). In order to ensure there is no contamination during germination, the effects of different surface sterilizing treatments were examined. Sodium hypochlorite at 0.3% (v/v) concentration was able to inhibit mold growth in adzuki bean, soybean and chickpea. Only 0.1% (v/v) sodium hypochlorite was needed to inhibit mold growth in black eye pea and petai, while mung bean required 0.05% (v/v) sodium hypochlorite to inhibit mold growth. 5’-PDE activity was determined using thymidine 5’-monophosphate p-nitrophenyl ester as substrate at pH 7.0 and 55°C. The formation of nucleotide monophosphates, the products of reaction, was determined at 405 nm. As a strong presence of phosphomonoesterase (PME) will reduce the yield of nucleotide monophosphates as the enzyme hydrolyzes these products into nucleosides and orthophosphate, PME activity was also determined using p-nitrophenyl phosphate as the substrate at 60°C and pH 5.0. Adzuki bean was found to have the highest 5’-PDE activity when germinated for 15 days. 5’-PDE has an optimum pH and temperature of 8.5 and 80°C, respectively. It was stable between pH 7.0 - 8.5. A higher stability was observed at pH 7.5 compared to pH 8.5, and at 60 and 65°C, the enzyme still possessed good catalytic function even after 4 days of incubation. EDTA, Triton X-100 and sodium dodecyl sulfate (SDS) strongly inhibited 5’-PDE activity (inhibition ranged from 75.2-99.4 %), while Tween 80 and Tween 20 were only slightly inhibitory. The enzyme was activated by Ca2+ up to 249%, K+, Mg2+ and Li+, when the final concentration of the cations was 10 mM. On the other hand, Na+,Zn2+, Ni+, Hg+, Cu2+, Pb2+, Fe2+, Al3+, Ba2+ and Co2+ at the same final concentration were inhibitory. 5’-PDE activity increased with an increase in the concentration of Li+, Na+ and Mg2+, until it reaches its maximum at 6 mM followed by a decrease in activity at concentrations beyond 6 mM. The presence of Ca2+ in the reaction mixture resulted in a similar trend, but the difference is that maximum activation occurred at 4 mM. K+, however, increased the activity of 5’-PDE from 0-10 mM. Al3+ decreased the activity of 5’-PDE activity as the concentration of the cation was increased. Thus, it is suggested that 5’-PDE from adzuki bean is a metallo-enzyme. The yield of 5’-PDE after the four purification steps (acetone precipitation, desalting,anion-exchange chromatography and gel filtration chromatography) was 13.37% with a purification fold of 6.7 and specific enzyme activity of 35.2 μmol p-nitrophenol/min/mg protein. The molecular weight of 5’-PDE using gel filtration chromatography was estimated at 125 kDa. Native PAGE analysis showed one major protein band, while SDS-PAGE estimated the molecular weight of the enzyme to be 124 kDa and indicated that the active/intact enzyme may be composed of two identical polypeptide chains (subunits) with a molecular weight of 62 kDa each. In conclusion, although 5’-PDE from adzuki bean has a high temperature optimum of 80 oC, the enzyme is more stable at 60oC, different cations affected the activity of the enzyme differently and the purified 5’-PDE has an estimated molecular weight of 124-125 kDa.